Pengembangan Media Pembelajaran Fisika Interaktif Berbasis Macromedia Flash Pro CS6 untuk SMA pada Pokok Bahasan Kinematika - Alhidayatuddiniyah T W; Ria Asep Sumarni; Siwi Puji Astuti (Universitas PGRI Semarang, 2018)
The purpose of this research is to: (1) produce interactive media with animated kinematics based subject of Macromedia Flash Pro CS6 for SMA and (2) to know the quality and feasibility of kinematics learning media product. The subject of kinematics in the subject of physics is abstract so that teachers and students need interactive media for teaching and learning activities and practice questions independently. The research method used refers to the ADDIE model with the research instrument using the assessment sheet by the material experts, media experts, and 10th grade students of SMAN 92 Jakarta and SMAN 115 Jakarta. The material of this research product is adjusted to the standard of competence by displaying GLBB animation, free fall motion, upward vertical motion along with its formulas, and practice questions. The results of the assessment by material experts, media experts, and students of SMAN 92 Jakarta and SMAN 115 Jakarta as much 98.61%, 93.75%, 92.17%, and 92.75%. Based on the tests that have been done can be concluded that the media developed eligible to be used as an innovative learning resources.